POTENSI LITTER SIZE KELINCI DENGAN PENYUNTIKAN HORMON HCG (Human Chorionic Gonadotrophin) PADA LEVEL PAKAN TRADISIONAL - Sri Minarti (Faculty of Animal Science, Universitas Brawijaya, 2010)
The effect of HCG on litter size of rabbits with traditional diet was examined. Twenty four New Zealand White doe’s of 8 to 10 months of age were used. They were allotted to three treatments, namely H0 (no hormone), H1 (with 10 IU of HCG), and H2 (with 20 IU of HCG). The traditional diet consisting of grass fields and fine bran was used. In mid-gestation each treatment performed surgery on 50% of the total number of replications for the observation variable ovulation and embryo, while 50% of the remaining replications maintained continue to get another variable that was a lenght of gestation and the litter size.The results showed that the injection of HCG affected the number of ovulation (P <0.01), the number of embryos (P < 0.01), the number of the litter size (P < 0.01) and the long gestation (P<0.05) significantly. (JIIPB 2010 Vol 20 No 1: 92-97).Keywords: Rabbit, HCG, litter size